Investigating the Depolymerization Behavior of Structurally Modified Kraft Lignin in Deep Eutectic Solvents - Wenguang Li; Shubin Wu (BioResources)
Deep eutectic-like solvents (DESs) are ideal green solvents for achieving depolymerization of kraft lignin under mild conditions. In this study, the impact of changes in chemical structures in hardwood kraft lignin (HKL), softwood kraft lignin (SKL), hydroxypropyl-modified hardwood kraft lignin (PHKL), and acetylated hardwood kraft lignin (AHKL) on depolymerization was investigated. The results indicated that structural modification can effectively adjust the depolymerization reaction of lignin. Under the depolymerization conditions (150 °C, 3 h, CHCl:p-TSOH), the depolymerization extent of HKL was 44.8%, which was 9.4% higher than that of SKL (35.4%). It was found that after hydroxypropyl modification of phenolic hydroxyl in HKL, the depolymerization extent of PHKL decreased to 29.5%, confirming that phenolic hydroxyl was the key functional group promoting lignin depolymerization. Acetylation modification of HKL can effectively increase the lignin depolymerization extent from 44.8% to 54.2%. The experimental results of lignin model compound addition confirmed that acetylation modification can effectively inhibit condensation reactions. The GPC analysis showed that the average molecular weight (Mw) of depolymerized oil was less than 800 g/mol and had a narrow polydispersity index (Mw/Mn < 1.2), making it an important precursor for high-value applications such as the preparation of aviation fuel.